Tailored strategies for emergency ABO-incompatible living donor liver transplantation: a series of three cases - Nalini Kanta Ghosh; Kausar Makki; Yogesh Yadav; Tathagata Karan; Piyush Srivastava; Anil Agarwal; Vivek Vij (Clinical Transplantation and Research)
ABO-incompatible (ABOi) living donor liver transplantation (LDLT) carries a substantial risk of antibody-mediated rejection (AMR) in both the short and long term. However, when no ABO-compatible donor is available, ABOi LDLT can be a viable option for patients with liver failure requiring emergency transplantation. To prevent AMR, various strategies have been implemented. However, typically, a pretransplant preparation period of at least 2 to 3 weeks is required to reduce the CD19+ or CD20+ cell count and antibody levels to an acceptable threshold (1:64). In emergency ABOi cases, due to time constraints, the desensitization protocol must be modified in accordance with the patient’s needs. We present a series of three cases involving emergency ABOi LDLT: one of primary graft nonfunction and two of acute-on-chronic liver failure. The goal was to achieve both short- and long-term rejection-free outcomes. Each case required different protocols based on the patient’s antibody titer, clinical condition, and intraoperative findings, and postoperative immunosuppression regimens were also individualized according to each patient’s clinical condition. This case series demonstrates the safety and feasibility of emergency ABOi LDLT with modifications to the desensitization protocol. However, further research into emergency ABOi transplantation is necessary to establish recommendations for managing such patients.